Empowering the Poor : Engaging Civil Society in World Bank Operations - World Bank (Washington, DC, 2012)
The beginning of the new millennium finds the Latin America and Caribbean region having made progress on several fronts. Health and education indicators continue to improve and all but one country hosts democratically elected governments. However, poverty rates are still high - 34.6 percent in 1998 compared to 33.4 percent in 1986, and extreme poverty is up from 14.4 percent in 1986 to 16.1 percent in 1998. Inequality is growing in many countries. In addition, corruption continues to haunt the region and there is a perception, at least among the poor, that reform programs have not delivered on their promises and that they are increasingly being excluded from markets, good quality public services and decision-making processes that affect their lives1. This has led to a lack of confidence in public institutions and decision makers in many countries, as well as a feeling of despair which manifests itself in a variety of ways throughout the region.